2012
DOI: 10.1111/j.1464-5491.2012.03701.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of culturally competent diabetes care interventions for improving diabetes‐related outcomes in ethnic minority groups: a systematic review

Abstract: Aim: To examine the evidence on culturally-competent interventions tailored to the needs of people with diabetes from ethnic minority groups.Methods: Medline (NHS Evidence), CINAHL and reference lists of retrieved papers were searched from inception to September 2011 and two NHS specialist libraries. Google, Cochrane and DARE databases were interrogated, and experts consulted. Studies were included if they reported primary research on the impact of culturally-competent interventions on outcome measures of any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 33 publications
6
101
0
1
Order By: Relevance
“…We found that 'any structured intervention, tailored to ethnic minority groups by (Zeh et al, 2012(Zeh et al, , p. 1237. This strengthens the case for further exploring and understanding specific cultural barriers to diabetes healthcare provision.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that 'any structured intervention, tailored to ethnic minority groups by (Zeh et al, 2012(Zeh et al, , p. 1237. This strengthens the case for further exploring and understanding specific cultural barriers to diabetes healthcare provision.…”
Section: Methodsmentioning
confidence: 99%
“…The screening and mapping exercise for the papers identified as a result of the search strategy (see Table 1) identified two issues, namely cultural barriers preventing members of ethnic minority groups from accessing effective diabetes care services, which is the focus of this review, and culturally competent healthcare interventions in ethnic minority groups with diabetes, which has been published elsewhere (Zeh et al, 2012). We found that 'any structured intervention, tailored to ethnic minority groups by (Zeh et al, 2012(Zeh et al, , p. 1237.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations